Hubungan Sikap Belajar Dengan Hasil Belajar Siswa Pada Mata Diklat Produktif Siswa Program Keahlian Teknik Gambar Bangunan SMK Negeri 1 Tanjung Raya Kabupaten Agam - 395-404 , Rikky Putra (CIVED, 2014)
ABSTRACT   This research is aimed to know the relationship between student’s learning attitudes toward student’s learning result Majoring on Building Drawing Engineering. The hypothesis is, “There is a relation between the student’s learning attitude toward learning result of student’s in grade X and XI Majoring on Building Drawing Engineering at SMK Negeri 1 Tanjung Raya. The type of the research is descriptive correlation. The samples were taken by using total sampling in 56 students grade X and XI Majoring on Building Drawing Engineering. The data were taken using a Likert scale questionnaire. The variable (X) is the student’s learning attitude and the variable (Y) is the student’s learning result. Data analysis was performed in three steps: (1) Data description, (2) Pre-testing analysis, (3) Hypothesis testing. This research is analyzed by using SPSS 21 program. Based on the data analysis, it is assumed that the Pearson correlation value is 0,603 and the significance value of the correlation which is 0,000 is less than 0,05. The result on student’s learning attitude is 79,02%. It means that there is a significant relationship between the student’s learning attitude toward the student’s learning result of student’s in grade X and XI Majoring on Building Drawing Engineering at SMK Negeri 1 Tanjung Raya. Keywords: learning attitude, learning result